Reconstruction of The Concept of Shirk in the Digital Era: A Thematic Analysis of the Qur’an on the Shift of Contemporary Aqidah - Firdaus Sinatra Firdaus Sinatra; Amrul Ahmad; Agung Pranoto Kadiatmaja (Journal of Education, Linguistics, Literature and Language Teaching, 2026)
In the contemporary post-secular landscape, the manifestation of shirk (polytheism) has evolved from overt ritualistic idol-worship to subtle, functional equivalents within digital culture. This study aims to reconstruct the Qur’anic concept of shirk by examining its modern implications on the purity of aqidah (faith). Using a qualitative-descriptive approach grounded in library research, this study employs Tafsir Mawdu’i (thematic interpretation) to analyze relevant Qur'anic verses alongside modern sociological theories of digital alienation and self-apotheosis. The findings reveal that digital culture—characterized by algorithmic dependence, the sanctification of "likes/validation," and the commodification of the self—mirrors the Qur’anic warnings regarding al-hawa (whims) and andad (rivals to God). This research identifies a shift from "theological shirk" to "functional shirk," where technological and social platforms exert an ultimate agency over human behavior. The study concludes that maintaining aqidah in the digital age requires a conceptual expansion of tawhid that addresses the psychological and systemic idols of the 21st century. The analysis draws specifically on classical and contemporary tafsir sources, including Tafsir Ibn Kathir and Tafsir Al-Mishbah, which anchor the interpretive lineage informing this study.